Morphological and productivity comparison between commercial and wild isolates of Pleurotus eryngii (D.C.: Fr.) Quél - Castronuovo, Donato; Mang, Stefania M.; Becce, Antonella; Candido, Vincenzo; Cardone, Loriana; Camele, Ippolito (Italian Journal of Agronomy, 2019)
Seven commercial isolates of Pleurotus eryngii (‘142 F’, ‘142 E’, ‘D +’, ‘V turbo’, ‘V 142’, ‘A12’ and ‘V160’), identified on molecular basis, were compared to five wild type isolates (‘Albino beige chiaro 1094’, ‘Altamura 1603’, ‘Albino 1107’, ‘Muro Lucano 139’ and ‘Conversano 1250’) concerning their morphological, productivity and quality features. Interestingly, two wild type isolates (‘Albino 1107’ and ‘Conversano 1250’) resulted more productive then all the commercial fungal isolates analysed. Besides, all wild isolates of P. eryngii showed harvest earliness and among them ‘Altamura 1603’ and ‘Conversano 1250’ were the best. The highest percentage of large basidioma was observed for the commercial isolates ‘V turbo’ and ‘D+’. Within the wild types, the isolate ‘Conversano 1250’ stood out. Regarding the pileus cuticle colour, commercial isolates (‘V turbo’ and ‘V 160’) showed lower lightness value than wild type isolates (‘Albino 1107’).